Contribution of petrophysical analysis and 3D digital survey in the archaeometric investigations of the Emperor Hadrian’s Baths (Tivoli, Italy) - Columbu, Stefano (2015)
This work studies the Heliocaminus Baths. From an architectural point of view, this is a special and unique building in the complex of the Hadrian’s Villa in Tivoli. This research is carried out with a multidisciplinary approach combining petrophysical, petrographic and min- eralogical characterization with the techniques of digital survey. The purpose of the research is to contribute to the understanding of Roman construction through the study of materials and from architectural aspects. Using mineral- petrographic and physical analysis, a set of samples (mortars and stones) was investigated for composition and physical properties (density, porosity, water absorption, mechanical strength, etc.). In the case of mortars, these parameters, together with the particle size distribution andthe binder/aggregate ratio determined in two ways using image analysis (on thin sections and on specimens), have shown a relationship between the physical and composi- tional characteristics and the function of mortars within the structure of the Heliocaminus Baths. However, in some cases, different characteristics were detected between the mortars belonging to the same masonry and with same function in the building, showing a slight inhomogeneity in the production of mortars. Furthermore, some relationships between compositional, physical aspects (i.e. porosity, sorting and size of aggregate) and mechanical strength have been found. All the gathered data, linked to the point cloud 3D model, allowed an accurate location of the traces from the construction story of this structure.